Representasi Ruang Pembebasan dan Pemberdayaan: Telaah Sosiologis pada Agensi Sozo Creative Lab dalam Perspektif Development of Freedom Amartya Sen - Kamiliyana, Ayu Asih; Salsabilla, Nazwa Reina (Fakultas Ilmu Budaya, Universitas Jambi, 2025)
This article discusses the Sozo Creative Lab's Creative Team Agency as a representation of a space of liberation and empowerment in the perspective of Development as Freedom by Amartya Sen. Starting from the phenomenon of increasing participation of the younger generation in the creative economy sector, this research examines how student groups are able to create alternative spaces that are not only economically oriented but also rich in values of autonomy, creativity, and capability development. Using a qualitative method with a phenomenological approach, data was obtained through observation and in-depth interviews. The study results show that Sozo Creative Lab as a creative agency can develop and utilize its capabilities as a representative embodiment of substantive freedom and social opportunity aspects as well as economic facilities as a form of instrumental freedom. The creative and collaborative process they undergo reflects a human development model that empowers, expands life choices, and demonstrates that development is not always about economic growth, but rather about how individuals are able to control their lives meaningfully. Abstrak Artikel ini membahas tentang Agensi Tim Kreatif Sozo Creative Lab sebagai representasi ruang pembebasan dan pemberdayaan dalam perspektif Development as Freedom oleh Amartya Sen. Berangkat dari fenomena maraknya partisipasi generasi muda dalam sektor ekonomi kreatif, penelitian ini menelaah bagaimana kelompok mahasiswa mampu menciptakan ruang alternatif yang bukan hanya bertujuan ekonomis, tetapi juga sarat nilai-nilai otonomi, kreativitas, dan pembangunan kapabilitas dalam kacamata sosiologi pembangunan. Menggunakan metode kualitatif dengan pendekatan fenomenologi, data diperoleh melalui observasi dan wawancara mendalam. Hasil kajian menunjukkan bahwa Sozo Creative Lab sebagai agensi kreatif mampu mengembangkan serta menggunakan kemampuannya sebagai perwujudan representatif dari kebebasan substantif dan aspek peluang sosial serta fasilitas ekonomi sebagai bentuk kebebasan instrumental. Proses kreatif dan kolaboratif yang mereka jalani mencerminkan model pembangunan manusia yang memberdayakan, memperluas pilihan hidup, serta memperlihatkan bahwa pembangunan tidak selalu soal pertumbuhan ekonomi, melainkan soal bagaimana individu mampu mengontrol kehidupannya secara bermakna.